A methods engineering study on Guiguinto Printing Press - Arceo, Ethel; Cirujales, Abigail Marie B.; Lim, Karenina F. (Diliman, Quezon City College of Engineering, 2000)
Guiguinto Printing Press was established in 1974. It started its operations at what was a junk shop. In 1976, it expanded to its present size, with the manager having bought the junk shop building, abolishing it, and building a bigger structure suited for a printing press. The company prints a wide variety of print jobs, from calling cards to newspapers. It is the largest printing press in town. Its customers include not only the town residents, but also come as far as Metro Manila. At present, the company operates with 13 machines and 10 workers. The company's present system was thoroughly studied in order to identify major problem areas. The main problem of the company is delay in production. This is due to poor facility layout, poor working conditions, the absence of the manager, lenient implementation of rules, and laxity of both workers and the management. The group recommends that the company assign a supervisor. This supervisor will be responsible for making sure that the jobs go through the production processes smoothly. This way, jobs are more likely to be finished on schedule. The group also recommends putting up whiteboards that contain the activities to be accomplished for a given day, so that workers will know what his tasks are for the day, and the order in which he should finish it. The group recommends increasing the number of fluorescent lamps in the work area in order to improve lighting. The group also recommends addition of exhaust fans, which will increase ventilation, and thus improve working conditions. In order to improve worker morale, the group also recommends putting up motivational posters. In order to facilitate smoother flow of materials, the group recommends changes in the layout, particularly the rearrangement of machines in the working area. Another recommendation is the use of panel dividers in order to separate the living area from the working area. In this way, the workers will not be distracted during work hours. The group recommends that the company invest in a moving table. This will be useful when moving material from one work area to the next. The group also recommends improving the toolbox by drawing the outline of each tool. This will ensure order and will immediately show if anything is missing. The group also recommends that the company combine some of its forms.
IE 32
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 32 : Methods Engineering
Keywords: Systems analysis